Patients’ and informal caregivers’ perspectives on self-management interventions for type 2 diabetes mellitus outcomes: a mixed-methods overview of 14 years of reviews - Ena Niño-de-Guzman Quispe; Javier Bracchiglione; Marta Ballester; Oliver Groene; Monique Heijmans; Laura Martínez García; Janneke Noordman; Carola Orrego; Claudio Rocha; Rosa Suñol; Pablo Alonso-Coello (Archives of Public Health, 2023)
Abstract Background Self-management interventions (SMIs) are core components of high-quality care in type 2 diabetes mellitus (T2DM). We aimed to identify and summarise the scientific evidence exploring the perspectives of patients with T2DM and their informal caregivers on outcomes of SMIs, and the key themes to enhance T2DM patient-centred care. Methods We conducted a mixed-methods overview of reviews. We searched MEDLINE, CINAHL and PsycINFO, up to June 2021 for systematic reviews (SRs) exploring the perspectives of adults with T2DM and their informal caregivers, regarding self-management. Two reviewers conducted independently study selection, data extraction and quality assessment. We estimated the degree of overlap across SRs. We performed a qualitative analysis using a thematic synthesis approach. Results We identified 54 SRs, corresponding to 939 studies, with a slight overlap. Most SRs (47/54, 87%) were considered high quality. We developed summaries for 22 outcomes and identified six overarching themes: (1) diabetic identity; (2) accessing healthcare; (3) experience of care; (4) engagement with self-management; (5) outcomes awareness; and (6) challenges adhering to self-management. We found important variability in how patients with T2DM and their informal caregivers value critical outcomes influenced by the disease progression and several contextual factors. Conclusions Our findings represent what matters most to patients with T2DM and their informal caregivers regarding outcomes of SMIs. Our results can facilitate the development and evaluation of SMIs, and guide decision-making in diabetes care, including the formulation of decisions and recommendations.